If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(4x + 2) = 250 Reorder the terms: 5(2 + 4x) = 250 (2 * 5 + 4x * 5) = 250 (10 + 20x) = 250 Solving 10 + 20x = 250 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 20x = 250 + -10 Combine like terms: 10 + -10 = 0 0 + 20x = 250 + -10 20x = 250 + -10 Combine like terms: 250 + -10 = 240 20x = 240 Divide each side by '20'. x = 12 Simplifying x = 12
| -3*3-9*-3= | | (3/8)/(2/3) | | -4=-4(-m-2) | | (64a^3*b^-6)^2/3 | | (64a^3b^-6)^2/3 | | x^3-2x-1=0 | | 2(-x+3)+5x= | | -3(4x-6)+8x=-6 | | 28=3-5x | | 6(15.2)+20=y | | 10x^2+[-2]+3x^2+5x+5= | | -3*3-9*3= | | 49=7-7x | | -7(-5x+7)=56 | | -3*3-9(3)= | | 2(-x+3)+5= | | -4x+172=6x+20 | | 2x-5/2=3x/2 | | -3(-8k+1)=45 | | -4(1+2x)=84 | | -9*(-45)+5y=-45 | | 7(2+4x)=238 | | 5c=78 | | 2(6x+5)=94 | | x+8(x+2)=5-x | | 192/-12 | | -9x+5*(-45)=-45 | | 4x-1(x-1)=-(x-1)+3x | | 2(3x-5)+x=12x-41solve | | a/2+a/3+a/4 | | 1/2*1/3 | | 3(6-x)=12 |